Acute proximal left anterior descending artery occlusion with de Winter sign - ÇİNÇİN, AHMET ALTUĞ; SARI, İBRAHİM; TİGEN, MUSTAFA KÜRŞAT (W B SAUNDERS CO-ELSEVIER INC, 2014)
Prompt recognition of electrocardiographic signs of acute coronary occlusion is essential for timely restoration of flow. ST-segment elevation or new onset left bundle-branch block are the most common electrocardiographic changes seen in acute phase of coronary occlusion. However, some patients may present with atypical electrocardiographic signs, and early diagnosis of these patients may constitute a clinical challenge. Here, we report a 41-year-old man presenting with an atypical electrocardiographic manifestation despite angiographically confirmed acute thrombotic occlusion of proximal left anterior descending artery.